Proposta de protocolo de avaliação de gestão ambiental de rodovias em operação para conservação da fauna - Queiroz, Camila Savastano de (2018)
The highways are highly impacting enterprises, with peculiar characteristics to the linear enterprises and capable of causing imbalance in the physical, chemical and biological environments of the ecosystems. The growth of the Brazilian road network is a great challenge for the conservation of ecosystems and the regulation of their impacts, especially in relation to those suffered by wildlife during the operation of highways. Although there is an environmental licensing process of the highways in the country, the advances achieved by road ecology in the mitigation area of the environmental impacts of the highway operation on the fauna, are not being considered by the current legislation. Therefore, describes the main environmental impacts caused by roads on wildlife and it created a methodology for the development of a protocol to evaluate the environmental performance of road infrastructure projects in oper ation, taking as reference the assessment of mitigation of these impacts.